Comparison of the Seven Interleukin-32 Isoforms’ Biological Activities: IL-32θ Possesses the Most Dominant Biological Activity - Shim, Saerok; Lee, Siyoung; Hisham, Yasmin; Kim, Sinae; Nguyen, Tam T.; Taitt, Afeisha S.; Hwang, Jihyeong; Jhun, Hyunjhung; Park, Ho-Young; Lee, Youngmin; Yeom, Su Cheong; Kim, Sang-Yeob; et al. (Frontiers in Immunology, 2022)
Cytokines are significantly associated with the homeostasis of immune responses in health and disease. Interleukin-32 (IL-32) is a cytokine originally discovered in natural killer cell transcript 4. IL-32 with different disorders has been described in terms of pathogenesis and the progression of diseases. Clinical studies have investigated IL-32 under various conditions, such as viral infection, autoimmune diseases, inflammatory diseases, certain types of cancer, vascular disease, and pulmonary diseases. The high expression of IL-32 was identified in different tissues with various diseases and found to have multiple transcripts of up to seven isoforms. However, the purification and biological activities of these isoforms have not been investigated yet. Therefore, in this study, we purified and compared the biological activity of recombinant IL-32 (rIL-32) isoforms. This is the first time for seven rIL-32 isoforms (α, β, δ, γ, ϵ, ζ, and θ) to be cloned and purified using an Escherichia coli expression system. Next, we evaluate the biological activities of these seven rIL-32 isoforms, which were used to treat different types of cells by assessing the levels of inflammatory cytokine production. The results revealed that rIL-32θ possessed the most dominant biological activity in both immune and non-immune cells.